Serological and Molecular Phylogenetic Detection of Coxiella burnetii in Lactating Cows, Iraq - Gharban, Hasanain A.J.; Yousif, Afaf A. (The Iraqi Journal of Veterinary Medicine, 2020)
This study is carried out to investigate the prevalence of Coxiella burnetii (C. burnetii) infections in cattle using an enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) assay targeting IS1111A transposase gene. A total of 130 lactating cows were randomly selected from different areas in Wasit province, Iraq and subjected to blood and milk sampling during the period extended between November 2018 and May 2019. ELISA and PCR tests revealed that 16.15% and 10% of the animals studied were respectively positive. Significant correlations (P<0.05) were detected between the positive results and clinical data. Two positive PCR products were analyzed phylogenetically, named as C. burnetii IQ-No.5 and C. burnetii IQ-No.6; and then recorded in the National Center for Biotechnology Information (NCBI) under an accession numbers of MN473204.1 and MN473205.1. Comparative identity of the local strains with NCBI-BLAST strains/isolates revealed 97% similarity and 0.1-0.6% of total genetic mutations/changes. NCBI-BLAST Homology Sequence reported high significant identity (P<0.05) between the local, C. burnetii IQ-No.5 and C. burnetii IQ-No.6; strains and C. burnetii 3345937 (CP014354.1) Netherlands isolate at 99.10% and 99.06%, respectively. The current study concluded that the percentage of infected cows with coxiellosis is relatively high, and Coxiella should be listed as abortive pathogen. Therefore, additional studies should be performed including different animals, samples, and regions.